Phakomatoses and cutaneous manifestations associated with moyamoya disease and syndrome - Tomaszewska, Maja; Strzelczuk-Judka, Lidia; Ostalska-Nowicka, Danuta; Jończyk-Potoczna, Katarzyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Phakomatoses are a group of neurocutaneous disorders whose origin is derived from the embryonic ectoderm. These disorders affect the central nervous system, the eyes, and the skin. This article presents phakomatoses and cutaneous manifestations associated with moyamoya disease and syndrome. Moyamoya disease is a progressive and occlusive disorder of the cerebral vasculature often presenting with particular phakomatoses. This article aims to reveal why patients with phakomatoses qualify for detailed neuroimaging.